Nocturnal ground level ozone at the rural station Stará Lesná, Slovakia - BIČÁROVÁ, Svetlana (Contributions to Geophysics and Geodesy, 2008)
Study of ground level ozone (O3) behaviour in the nocturnal boundary layer is important from the point of view of O3 progress after sunrise. Data of the EMEP database obtained by O3 measurement at rural station Stará Lesná for time period 1992–2005 are used for the investigation of the seasonal variation and relationship between nocturnal and peak daylight O3 concentration. Seasonal variability of nocturnal O3 values (22–04 h UTC) ranges between 40 μg m–3 for the autumn-winter and 80 μg m–3 for the spring months. On the other hand, hourly course of O3 concentration indicates the substantive night O3 depletion during the spring-summer season, particularly in May. Results of analysis show relevant linear relationship for seasonal O3 variables: (y) - negative difference between nocturnal and daily O3 value, (x) - positive difference between daylight peak and daily O3 values. It is assumed that lower daylight O3 peak is linked with higher nighttime O3 concentration, and vice versa. The increase of nocturnal O3 level demonstrates also the simulation considering 15% reduction of peak daylight O3 values. Furthermore, the simulation documents minimally the affect of O3 peak reduction on the mean daily O3 values. The achieved results suggest that the decrease of the highest O3 concentrations as a consequence of anthropogenic emissions reduction can be compensated by increase of nocturnal O3 values with marginal impact on the mean O3 values. The growth of nocturnal O3 values due to lower daylight O3 peak in the spring-summer season, as well as slight removal by surface deposition and long-lasting persistence of air pollution during winter can enrich the background O3 level. Further investigation will be needed to explain the nocturnal O3 contribution to background O3 concentration.